"War and Peace" of Ukrainian Tourism: The Impact of Geopolitical Factors on the Tourism Process in Ukraine - Parfinenko, Anatoliy; Прфіненко, Анатолій Юрійович (Львів : Львівський національний університет імені Івана Франка, 2019)
The article intends to highlight geopolitical aspects in the development of international tourism in Ukraine as a global phenomenon that carries out economic, social and international political action. The paper analyzes international tourist flows in Ukraine, their dynamics and spatial structure during 2000–2017 in particular, in the context of military-political aggression on the part of Russia and intensification of Ukrainian-Russian intergovernmental relations. It has been established that the current dynamics of the international tourist flow in Ukraine is characterized by a sharp decrease in the volume of international visitors, a decrease in the rates of development of tourism activity and the reformatting of the spatial structure of the inbound and outbound tourist flow. The question arises as to the expediency of tourism development during the military-political сonfrontation. The experience of holding Eurovision–2017 in Ukraine, which took place against the backdrop of the anti-terrorist operation, is highlighted. The conclusion is drawn about the constructive role of tourism as a factor of «soft power» that can influence the informing of the world about the «Ukrainian issue». In this sense, international tourist flows acted as channels of public diplomacy, reflecting the true situation in Ukraine, which is fundamentally different from the Russian mass media. Attention is drawn to the intensification of domestic tourism in Ukraine, taking place against the backdrop of deteriorating key indicators of economic and social development. It is argued that the growth of the weight of domestic tourism was also possible due to the growth of patriotic sentiment in Ukrainian society. In a sense, the development of domestic tourism is seen as a continuation of the struggle of the Ukrainian people for their independence and territorial integrity. Consequently, the constructive role of tourism lies not only in the presentation of the country to the world community, but also in the construction of a national identity within the country. In this way domestic tourism favors further development of the Ukrainian political nation.
"Війна і мир" українського туризму: вплив геополітичних чинників чинників на туристичний процес в Україні
Висвітлено геополітичні аспекти розвитку міжнародного туризму в Україні як глобального явища, що здійснює економічну, соціальну та міжнародно-політичну дію. Туристичні потоки розглядаються як глобальний простір соціальних мереж і відповідних економічних й геополітичних впливів. Стверджується, що просторова структура туристичних прибуттів відображає і впливає на тенденції міжнародної взаємодії. Охарактеризовано роль та місце України на міжнародному туристичному ринку з урахуванням російської окупації Автономної республіки Крим. З’ясовано, що протягом останніх десяти років Україна перетворилася на привабливу туристичну дестинацію, яка за кількістю міжнародних туристичних прибуттів (близько 25 млн) увійшла до десятки найвідвідуваніших країн світу. Здійснено аналіз міжнародних туристичних потоків в Україні, зокрема їх динаміку та просторову структуру протягом 2000–2017 рр. в контексті військово-політичної агресії з боку Росії та загострення українсько-російських міждержавних відносин. Встановлено, що сучасна динаміка міжнародного туристичного потоку в Україні характеризується різким зменшенням обсягів міжнародних відвідувачів, зниженням темпів розвитку туристичної діяльності та переформатуванням просторової структури в’їзного та виїзного туристичного потоку. Розглянуто питання щодо доцільності розвитку туризму під час військово-політичного протистояння. Висвітлюється досвід проведення Україною Євробачення–2017, яке відбувалося на тлі проведення антитерористичної операції. Робиться висновок про конструктивну роль туризму як чинника «публічної дипломатії», здатного впливати на інформування світу щодо «українського питання». В цьому сенсі міжнародні туристичні потоки виступили як канали публічної дипломатії, що відобразили справжню ситуацію в Україні, яка докорінно відрізняється від подання російськими ЗМІ. Робиться висновок, що міжнародний туризм є не тільки споживачем туристичних ресурсів, а й активним економічним та політичним актором, який вступає у «діалог» з об’єктивно-статичним географічним простором, політизує його, створює передумови як для прояву соціокультурної конфліктності, так і для забезпечення миру і міжкультурного діалогу.
Keywords: international tourism; actors of geopolitical influence; Russia–Ukraine international relations; regional structure of tourism flows in Ukraine; public diplomacy